Anterior Ischemic Optic Neuropathy and Branch Retinal Artery Occlusion: An Uncommon Finding in Thalassemia Minor - Soukaina Belfaiza; Adil El Khouya Ali; Imane Jeddou; Taoufik Abdellaoui; Karim Reda; Abdelbar Oubaaz (Indian Journal of Medical Specialities)
The minor thalassemia has always been considered as an asymptomatic disease in the majority of cases. However, according to the literature, the poor chronic retinal perfusion related to a minor thalassemia can produce ocular manifestations as venous occlusion and ischemic retinopathy, especially in the presence of other risk factors. This short report describes a rare observation of a patient with an anterior ischemic optic neuropathy and branch retinal artery occlusion revealing a minor beta-thalassemia.